Pengaruh Kesehatan Mental Dan Kesehatan Spiritual Terhadap Indeks Prestasi Kumulatif (IPK) Mahasiswa Pendidikan Agama Islam Institut Agama Islam Negeri Ponorogo - Mauridhatul Kasanah; Retno Widyaningrum (PT. Pusmedia Group Indonesia, 2024)
Nowadays there are many cases of mental health and spiritual health disorders, such as stress, depression and even many cases of student suicide due to being burdened by coursework and other things. Apart from that, there are several previous studies which state that the mental health and spiritual health of students can influence several things, including the student's GPA. Based on this, researchers will examine the influence of mental health and spiritual health on the GPA of PAI IAIN Ponorogo students. This research uses a quantitative type of research with questionnaire data collection techniques distributed via Google Form, data analysis techniques in the research use multiple linear regression tests. The results of this research found that a significance test value of 0.000 indicated that there was a significant influence of mental health and spiritual health on student GPA scores. The average mental health score of respondents was 19.95, while the average spiritual health score of students was 30.35. Furthermore, the GPA value has an average of 3.43. With an R Square value of 0.143, it can be concluded that 14% of the GPA value is explained by mental health and spiritual health variables. From this data, it can be concluded that the better the student's mental and spiritual health level, the higher the student's GPA and achievement. Keywords: Mental Health; Spiritual Health; IPK